2004
DOI: 10.1016/j.jebo.2003.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Trust responsiveness and beliefs

Abstract: Trust responsiveness is "a tendency to fulfil trust because you believe that it has been placed on you" [Is trust self-fulfilling? An experimental study. Discussion Paper no. 76 (October), Department of Economics, University of Oxford, 2001]. We use two simple trust games to measure directly or indirectly the robustness of trust responsiveness in three conditions: when beliefs are elicited and a summary of these beliefs is transmitted, when beliefs are elicited but not transmitted, when beliefs are not elicite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(60 citation statements)
references
References 3 publications
(2 reference statements)
3
55
0
Order By: Relevance
“…The framework of dynamic psychological games (Battigalli and Dufwenberg (2009)) incorporates many of these earlier approaches, including the notion that people suffer from guilt when they disappoint what they think are other players' expectations. 2 For experimental evidence on the impact of belief-dependent preferences in trust, dilemma and principal-agent games see also Guerra and Zizzo (2004), Falk and Kosfeld (2006), Dufwenberg et al (2011) and Charness and Dufwenberg (2011). Vanberg (2008) investigated potential reasons behind the positive effect of promises on trustworthy behavior found in Charness and Dufwenberg (2006) and concluded that preferences for promise-keeping rather than preferences for meeting expectations might be the predominant driver of the results.…”
Section: Introductionmentioning
confidence: 99%
“…The framework of dynamic psychological games (Battigalli and Dufwenberg (2009)) incorporates many of these earlier approaches, including the notion that people suffer from guilt when they disappoint what they think are other players' expectations. 2 For experimental evidence on the impact of belief-dependent preferences in trust, dilemma and principal-agent games see also Guerra and Zizzo (2004), Falk and Kosfeld (2006), Dufwenberg et al (2011) and Charness and Dufwenberg (2011). Vanberg (2008) investigated potential reasons behind the positive effect of promises on trustworthy behavior found in Charness and Dufwenberg (2006) and concluded that preferences for promise-keeping rather than preferences for meeting expectations might be the predominant driver of the results.…”
Section: Introductionmentioning
confidence: 99%
“…25 Regressions 1 and 3 in Table 3 show that the introduction of groups per 23 We have also run random effects regressions getting the same broad picture in terms of mean giving rates, whereas estimates of regressions on mean return rates collapses to OLS estimates due to zero variance being explained by the session level random coefficients; this leaves OLS with error clustering as the better estimation option. 24 This might occur for a number of psychological motives which have been documented in other experiments, such as inequality aversion (Fehr and Schmidt 1999), reciprocity (Falk and Fischbacher 2001) or trust responsiveness (Guerra and Zizzo 2004). 25 Each round average level for each session was the unit of observation that was matched with period number for computing these correlations.…”
Section: Results 1 Low Status Subjects Trust Less Other Low Status Submentioning
confidence: 90%
“…Erev et al (1993) find that eliciting beliefs about the probability of events diverts attention from the size of payoffs and reduces expected value maximization. Guerra and Zizzo (2004), on the other hand, find no effect of belief elicitation on trusting behavior. Hoffmann (2013) compares an action-only treatment with a treatment where beliefs are elicited simultaneously, and finds that belief elicitation makes subjects less likely to choose dominated actions.…”
Section: Table 2 About Herementioning
confidence: 86%